2020
DOI: 10.1016/j.crstbi.2020.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Shotgun EM of mycobacterial protein complexes during stationary phase stress

Abstract: There is little structural information about the protein complexes conferring resistance in Mycobacterium tuberculosis (Mtb) to anti-microbial oxygen and nitrogen radicals in the phagolysosome. Here, we expose the model Mycobacterium, Mycobacterium smegmatis, to simulated oxidative-stress conditions and apply a shotgun EM method for the structural detection of the resulting protein assemblies. We identified: glutamine synthetase I, essential for Mtb … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…An additional unique characteristic of several DyPs is their function as a cargo protein for encapsulin, a bacterial nanocompartment protein. One of the best-studied of these DyPs is MtDyP (class P) from Mycobacterium tuberculosis [ 13 , 26 ], a bacterium that slips through defenses generated by the host immune response and induces tuberculosis. MtDyP, which is shielded from oxidative stress in the nanocompartment through association with encapsulin, appears to play an important role in defending against the immune assault by virtue of its peroxidase activity.…”
Section: Physiological Role Of Dyp-type Peroxidasesmentioning
confidence: 99%
“…An additional unique characteristic of several DyPs is their function as a cargo protein for encapsulin, a bacterial nanocompartment protein. One of the best-studied of these DyPs is MtDyP (class P) from Mycobacterium tuberculosis [ 13 , 26 ], a bacterium that slips through defenses generated by the host immune response and induces tuberculosis. MtDyP, which is shielded from oxidative stress in the nanocompartment through association with encapsulin, appears to play an important role in defending against the immune assault by virtue of its peroxidase activity.…”
Section: Physiological Role Of Dyp-type Peroxidasesmentioning
confidence: 99%
“…Moreover, it has been shown that some encapsulin systems may possess multiple cargo proteins, which are made up of one core cargo protein and up to three secondary cargo proteins according to the TPs (6). Notably, a large proportion of native cargo proteins are DyP-type peroxidases, conferring the resistance of the cell to oxidative stress (6,7,11,(15)(16)(17)(18). However, to date, the structural information on the cargo-encapsulated encapsulins is not yet available (SI Appendix, Table S1), and thus, little is known about the structural arrangement and mechanistic features of the cargo proteins loaded in the encapsulins.…”
mentioning
confidence: 99%
“…Actinobacteria harbors the largest number of encapsulin or encapsulin-like systems (6). DyP-containing encapsulins have already been reported from mycobacteria, including Mycobacterium smegmatis (15) and Mycobacterium tuberculosis (19). These have been considered as potential biomarkers to detect active tuberculosis (TB) (20).…”
mentioning
confidence: 99%
“…Each of these three cargos has independent antioxidant activity and is encapsulated in the nanocompartment when coexpressed with the encapsulin gene in E. coli [76]. In M. tuberculosis cells grown in standard laboratory conditions, however, only nanocompartments with the core cargo Mt-DyP have been identified [77]; results are similar for M. smegmatis [54].…”
Section: Cargo Loadingmentioning
confidence: 89%
“…EMD-3608) [53]. An adapted shotgun electron microscopy method identified numerous protein complexes in M. smegmatis and were used efficiently to find new encapsulin nanocages [54].…”
Section: Nanocompartment Structurementioning
confidence: 99%